A comparative study of e-commerce bachelor degree programmes in US, UK, Australia, and selected Asian countries - Ahmi, Aidi (Universiti Utara Malaysia, 2004)
Fast growing trend in electronic business activities demands for professional in the related field. For the matter, higher learning institutions have been offering e-commerce-related programmers, which later raises e-commerce education issues. Firstly, whether to impact e-commerce skills into existing programmers such as into business or information technology (IT), or introduce e-commerce as a separate programmed and secondly, the faculty need to determine the best combination of e-commerce skills (technical versus non-technical) incorporated into the programmer. This study, therefore examines the characteristics and programmer content of Bachelor E-Commerce in selected regions around the globe. The list of universities that offer such programmer and its programmer detail are obtained from respective university's website. Findings of study reveal that there are variation on characteristics as well as contents of the programmer between regions and faculty-types (IT-based or business-based). Generally, most of e-commerce programmers are offered by concentration or majoring mode where business-based faculties have greater tendency to offer such programmers. It is also shown that the proportion of subject components required for the programmer (business, technical e-commerce, non-technical e-commerce and technical subjects) also depend on university's region as well as type faculty. Further analysis shows that faculty-tupes influence the decision whether to incorporate higher proportion of technical or non-technical subjects into programmer. It is expected that IT-based faculties offer higher percentage of technical subjects than business-based faculties and vice versa. Hence it can be concluded that variation in nature and contents of e-commerce bachelor degree programmer may be influenced by faculty-types as well as the programmer;s objectives.